Model Integrasi Supply Chain Management pada Industri Manufaktur-Jasa: Studi Kasus di Industri Otomotif - Nazwa Deasy Kamila; Febryansyah Putra Siregar; Bagas Prakasa (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This study uses a qualitative method to analyze the integration model of Supply Chain Management (SCM) in the manufacturing-service industry, focusing on a case study in the automotive sector. SCM integration in this context involves the coordination of production processes, distribution, and after-sales services to enhance efficiency and responsiveness to customer demands. Data were collected through in-depth interviews and direct observations at an automotive company implementing integration strategies between manufacturing and service operations. The findings show that cross-functional collaboration among suppliers, manufacturers, and service providers plays a vital role in creating an adaptive supply chain. Digital integration through connected information systems also significantly accelerates decision-making and improves overall supply chain visibility. This study highlights the importance of a holistic approach encompassing technical, organizational, and inter-partner relationship aspects. The results are relevant for automotive companies aiming to strengthen competitiveness through cross-sector SCM integration and serve as a reference for developing industrial policies that support collaboration between manufacturing and service actors in the Industry 4.0 era.